Evaluation of Complications of Midface Fracture Including the Orbital Floor - Rameet Sandhu; Vikas Sikarwar; Sushil Ojha; Dushyant Upadhyay; Amit Agarwal; Apoorva Sharma (Wolters Kluwer Medknow Publications, 2024)
Background: Choosing an appropriate course of treatment for midface fracture can be challenging due to the variable presentations of midfacial fractures and concurrent orbital floor injuries. Objectives: To evaluate complications of midface fracture including the orbital floor. Materials and Methods: It was a cross-sectional study carried out on 456 patients diagnosed with midface fracture, including the orbital floor, clinically and radiographically. The computed tomography radiograph of each study participant was evaluated. There was a thorough clinical assessment of each study participant. Results: There were complications like laceration (47.3%), hematoma (54.2%), infraorbital nerve paraesthesia (13.05%), Contusio bulbi (13.30%), and diplopia (13.35%). No complications were observed in 8.25% of study participants. The most common complication was laceration. Conclusion: The eyeball, orbit, soft tissues, and surrounding structures should be precisely examined clinically and radiologically in midface fractures.